Political communication today: challenges and threats (Communication & Society, 2017)
Events such as the triumph of Brexit in the United Kingdom, the victory of Donald Trump in the United States or the rise of populism in some European countries have resulted in a significant upheaval in the western political scenario, which had remained stable since the Second World War. These events have opened up new and relevant avenues for political communication. This discipline is facing important challenges and threats, from the academic and political action points of view. New phenomena, such as the loss of credibility of political actors and of the traditional means of communication, the trivialisation of politics, the use of algorithms to understand, anticipate and intervene in the development of communication or the rise of the new media in the public arena are being combined with old acquaintances such as persuasion, propaganda, customisation and mastering emotions. This article explores new lines of work, prospects, strategies and positioning and furthermore reflects on the possibilities offered by them for establishing future theoretical, methodological and action paths within a communicative realm characterised by its ongoing evolution within an increasingly uncertain and changing context.